2021
DOI: 10.31234/osf.io/eb2gt
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Information Delivered by a Chatbot Has a Positive Impact on COVID-19 Vaccines Attitudes and Intentions

Abstract: The COVID-19 vaccines will not end the pandemic if they stay in freezers. In many countries, such as France, COVID-19 vaccines hesitancy is high. It is crucial that governments make it as easy as possible for people who want to be vaccinated to do so, but also that they devise communication strategies to address the concerns of vaccine hesitant individuals. We introduce and test on 701 French participants a novel messaging strategy: a chatbot that answers people’s questions about COVID-19 vaccines. We find tha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…It is thus important to design interventions at all scales and, when large effects are required, to make the best of the power of discussion to change minds. For example, in a recent study, a chatbot designed to address arguments against the COVID-19 vaccine had proved successful in shifting vaccination attitudes and behavioral intentions [10].…”
Section: Test a Communication Campaign Addressing Vaccine Hesitancymentioning
confidence: 99%
See 2 more Smart Citations
“…It is thus important to design interventions at all scales and, when large effects are required, to make the best of the power of discussion to change minds. For example, in a recent study, a chatbot designed to address arguments against the COVID-19 vaccine had proved successful in shifting vaccination attitudes and behavioral intentions [10].…”
Section: Test a Communication Campaign Addressing Vaccine Hesitancymentioning
confidence: 99%
“…in person discussion [8,9], chatbot [10]). (ii) Identify the outcome of interest: vaccination rates, or proxies such as vaccination attitudes and intentions, or motivation to transmit pro-vaccination messages.…”
Section: Box 1 How To Test a Covid-19 Vaccine Messaging Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…As COVID-19 vaccination campaigns continue to target the general public, intelligent conversational agents have the potential to play a critical role in debunking misinformation surrounding vaccines and directing individuals to public health resources [ 21 , 22 ]. One study in the preprint stage, which examined a chatbot designed to address arguments against the COVID-19 vaccine, promisingly showed that individuals’ attitudes towards vaccination became more positive after receiving information from this chatbot [ 23 ]. Moreover, in a recent Nature survey of infectious disease researchers, virologists, and immunologists in 23 countries, the majority of respondents predicted that the SARS-CoV-2 virus will likely become endemic over time, with its future closely depending on virus mutations and the type of immunity individuals will acquire [ 24 ].…”
Section: Strengths Challenges and Future Directionsmentioning
confidence: 99%
“…We are aware of only one study which has used actual results from clinical trials as part of an experimental intervention. Altay et al (2021) paid French participants to spend 10 minutes interacting with an extensive Q&A interface in which users could select questions and read answers (the complete Q&A comprised more than 20 pages of text). Some of the answers included preliminary results from clinical trials outlining vaccine efficacy (95% for Pfizer/BioNTech and Moderna, and <70% for AstraZeneca) and noted some side effects without giving any indication of frequency.…”
Section: The Effect Of Covid-19 Vaccine Communications On Intentionsmentioning
confidence: 99%